2009
DOI: 10.3748/wjg.15.5784
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of Th17 cells in the pathogenesis ofinflammatory bowel disease

Abstract: The etiopathology of inflammatory bowel disease (IBD) remains elusive. Accumulating evidence suggests that the abnormality of innate and adaptive immunity responses plays an important role in intestinal inflammation. IBD including Crohn's disease (CD) and ulcerative colitis (UC) is a chronic inflammatory disease of the gastrointestinal tract, which is implicated in an inappropriate and overactive mucosal immune response to luminal flora. Traditionally, CD is regarded as a Th1-mediated inflammatory disorder whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 47 publications
3
98
1
Order By: Relevance
“…Our finding that CD26 ++ IL-17-producing T cells are highly enriched in the inflamed tissues compared with the peripheral blood (Fig. 6C, 6D) is in agreement with previous studies implicating a role of Th17 cells in the pathogenesis of these inflammatory diseases (26,35), particularly inflammatory bowel disease (36). Interestingly, high levels of CD26 have previously been associated with autoimmune diseases, such as multiple sclerosis and rheumatoid arthritis (10,11).…”
Section: Discussionsupporting
confidence: 80%
“…Our finding that CD26 ++ IL-17-producing T cells are highly enriched in the inflamed tissues compared with the peripheral blood (Fig. 6C, 6D) is in agreement with previous studies implicating a role of Th17 cells in the pathogenesis of these inflammatory diseases (26,35), particularly inflammatory bowel disease (36). Interestingly, high levels of CD26 have previously been associated with autoimmune diseases, such as multiple sclerosis and rheumatoid arthritis (10,11).…”
Section: Discussionsupporting
confidence: 80%
“…63,64 Th17 cells also have been suggested to play a key role in the pathogenesis of colitis and IBD, as they convert into Th1 cells and promote Th1 responses through IL-12 and IL-23. 65,66 We found that adoptive transfer of CD4 1 VEGFR1 2 CD25 2 T cells into RAG2-deficient mice resulted in colitis seven weeks after transfer, whereas the cotransfer of CD4 1 VEGFR1 1 CD25 2 T cells did not induce colitis. The most prominent histopathological changes by CD4 1 VEGFR1 2 CD25 2 T-cell injection into RAG-2 KO mice were cellular infiltration, absence of crypts, and hypertrophy of all the layers of the colon.…”
Section: Discussionmentioning
confidence: 89%
“…To date, the precise aetiology of CD remains unknown, but it is well established that there is an infiltration of inflammatory cells focally in the bowel, leading to the production of proinflammatory cytokines and propagation of the immune response [1][2][3]. With the recent discovery of the Th17 subset and Th17-associated cytokines, understanding of CD has expanded rapidly because these cells and cytokines have a critical role in the pathogenesis of CD [5][6][7]. Therefore, Th17-associated cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that CD bears all the stigmata of an exaggerated T helper type 1 (Th1) immune response, characterized by increased interferon (IFN)-g and IL-12 [2][3][4]. However, in past years published data have highlighted the critical role of the Th17 subset in the pathogenesis of CD, as well as the signature cytokine IL-17A, in the development of intestinal mucosal damage [5]. Th17 cells are a recently discovered addition to the Th cell ensemble, characterized by the expression of a cytokine family (IL-17A, IL-17F, IL-21, IL-22 and IL-26) and transcription factor retinoic acid-related orphan receptor C (RORC) [6].…”
Section: Introductionmentioning
confidence: 99%